Systematic literature review on performance drivers of Ph.D. success: utilizing PRISMA, TCCM, and an 8-step approach - Farhana Yeasmin (Cogent Education, 2024)
AbstractThe study systematically assesses the determinants impacting Ph.D. success, amalgamating insights from 38 meticulously curated studies. Through the integration of PRISMA, TCCM, and an 8-step process, it delineates crucial findings and factors influencing successful Ph.D. completion. The PRISMA diagram intricately outlines the data retrieval process, while the TCCM framework systematically organizes discoveries, emphasizing elements crucial to Ph.D. achievement, including timely completion. Previous studies encompassed 17 theories (T), five essential characteristics (C) or factors, nine distinct countries or contexts (C), and diverse methodologies (M) encompassing qualitative, quantitative, and mixed approaches. Institutional factors emerge as the most prominent within the corpus of 38 studies at 65.79%, followed by demographic, financial, and psychological factors at varying degrees, with social factors contributing minimally at 7.89% to Ph.D. progression. The research meticulously follows an 8-step process throughout its developmental trajectory, underscoring critical determinants impacting Ph.D. candidates’ satisfaction, advancement, and persistence. The study’s limitation lies in including 38 studies based on specific criteria. By consolidating prior works, conducting critical analysis, and comparing findings, it offers insights into factors affecting successful Ph.D. attainment, guiding institutions, policymakers, funders, and Ph.D. students. Additionally, it pioneers the field by advancing methodologies through integrating PRISMA, TCCM framework, and 8-step approaches, paving the way for future research endeavors.